Pengaruh Citra Merek, Promosi, dan Online Customer Review Terhadap Keputusan Pembelian Konsumen pada Shopee di Kota Bekasi - Maharani, Rani; Dananjaya, Irwandaru (Masyarakat Ekonomi Syariah Bogor, 2025)
The advancement of information technology has driven rapid development across various fields, including traditional, digital, and fundamental research methods. This study aims to analyze the effect of brand image, promotion, and online customer reviews on consumer purchase decisions on Shopee in Bekasi City, both partially and simultaneously. Primary data were collected from 200 respondents using a questionnaire with purposive sampling, and analyzed using SPSS through validity and reliability tests, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that brand image (t = 6.141; p < 0.001) and online customer review (t = 10.195; p < 0.001) have a significant partial effect on purchase decisions, while promotion also shows a significant partial effect (t = 5.289; p < 0.001). Simultaneously, these three independent variables significantly influence purchase decisions with F = 110.198; p < 0.001 and adjusted R² = 0.622, indicating that 62.2% of the variation in purchase decisions can be explained by these variables. These findings confirm that brand image, promotion, and customer reviews play a crucial role in enhancing consumer confidence and purchase decisions on Shopee in Bekasi City.